Econstructionist Analysis On the Relevance of Secondary School Curriculum Content in Promoting National Cohesion Among Students in Machakos Town Sub-County, Kenya - Mwanzia, Ruth Mutunge; Muthaa, George Mungiria; Ogola, Fredrick O. (My University, 2015)
Education is the primary means of promoting national cohesion, international cooperation as well as socio-economic development. Through school curriculum, education enables a country to achieve its needs and aspirations. Despite the comprehensive school curriculum, the country is faced with ethnic divisions, religious intolerance and violence and this raises concern on relevance of the school curriculum content in promoting national cohesion. The objective of this study was to investigate the relevance of secondary school curriculum content in promoting national cohesion. The study was based on the ideals and principles of a school curriculum as advocated by reconstructionism philosophy. Descriptive survey research design was adopted for the study. A sample size of four hundred and nine (409) respondents comprising of three hundred and sixty (360) student leaders, Forty eight (48) teachers and Sub-County Quality Assurance and Standards Officer (QASO) was used for the study. Purposive sampling was adopted to select the respondents. Questionnaires and interview schedule were used for data collection. The study established that the secondary school curriculum content gave the students little opportunity to reflect critically on issues affecting national cohesion which is attributed to lack of practical skills on issues related to national cohesion. The study recommends a review on secondary school curriculum content to reflect on emerging issues on national cohesion and integration. The findings of the study will provide critical information to all the educational stakeholders on the important role that the secondary school curriculum content plays in promoting harmonious living in the society.
Keywords: Reconstructionist analysis; Secondary school curriculum; Curriculum Content; National cohesion.